Emotional Intelligence and Employee Engagement: Evidence from Healthcare Workers in Sri Lanka - Nirojan, J.; Mayuran, L. (International Conference on Contemporary Management [ICCM]-2021], 2021)
The present study aims to investigate the impact of emotional intelligence on employee engagement among the healthcare workers. Employee engagement is critical for completing and executing activities in any form of organization. It is critical to provide organizations with the opportunity to be in a sustainable state for long-term sustainability, as well as to gain a competitive advantage over competitors. Employees must be able to recognize, use, and control their own feelings in productive ways in order to alleviate tension and resolve obstacles in the workplace. Employees' levels of commitment can be affected by emotional symptoms. They have the ability to lead either a higher or lower morale, which can have a positive or negative impact on employee engagement. Though previous studies, paid attention on engagement level, but little attention was paid with emotional intelligence of healthcare workers. In addition, this study sheds new light on the emotional intelligence level, engagement level, and effect of emotional intelligence on employee engagement among Sri Lankan healthcare employees. Survey method was used and data were collected from conveniently chosen 212 healthcare employees working in public and private hospitals. The results disclose that the individuals with high emotional intelligence are more likely to have high employee engagement. The theoretical and practical implications are discussed at the end of the paper.
Keywords: Emotional Intelligence; Employee Engagement; Healthcare workers; Hospitals